Answer:
unknown
Step-by-step explanation:
I am sorry but part of your question is missing
Answer:
(n + 1)(3n + 7)
Step-by-step explanation:
3n² + 10n + 7
Consider the factors of the product of the n² term and the constant term which sum to give the coefficient of the n- term.
product = 3 × 7 = 21 and sum = + 10
The factors are + 3 and + 7
Use these factors to split the n- term
3n² + 3n + 7n + 7 ( factor the first/second and third/fourth terms )
3n(n + 1) + 7(n + 1) ← factor out (n + 1) from each term
= (n + 1)(3n + 7) ← in factored form
Answer:
n<1.3
Step-by-step explanation:
-2.5n+8.7>5.45
add -8.7 on both sides
-2.5n>-3.25
divide both sides by -2.5
n<1.3 (after division inequality sign changes)
answer of Q2 is -4 2/3
answer of Q3 is -2/9
answer of Q4 is -23/3
answer of Q5 is 2^2. 3^2.5
Answer:
a. 18 b. 119°, 118°
Step-by-step explanation:
a. Given angles are vertical, so they are equal.
6a+11 = 2a+83
6a-2a = 83-11
4a = 72
a = 72/4
a = 18
b. Substituting the value of a in the given angles,
6a+11 = 6*18+11 = 108+11 = 119°
2a+83 = 2*18+83 = 36+83 = 118°